Why do peer reviewers decline to review manuscripts? A study of reviewer invitation responses. Issue 1 (20th January 2016) - Willis, Michael
Abstract: With peer review under closer scrutiny than ever before, research is needed to investigate not only what incentives encourage researchers to review manuscripts, but also what reasons prevent them from reviewing. We analysed responses to reviewer invitations sent by one journal in March to July 2015. The data showed that the overwhelming reason why reviewers decline is because they are unavailable to do so. Although the finding may not be surprising and confirms the findings of earlier research, the study illustrates how a journal can analyse and draw conclusions from its own reviewer invitation data as a first step to improving the invitation acceptance rates.